Kinetics coming into focus: single-molecule microscopy of riboswitch dynamics. Issue 9 (2nd September 2019) - Ray, Sujay; Chauvier, Adrien; Walter, Nils G.
ABSTRACT: Riboswitches are dynamic RNA motifs that are mostly embedded in the 5ʹ-untranslated regions of bacterial mRNAs, where they regulate gene expression transcriptionally or translationally by undergoing conformational changes upon binding of a small metabolite or ion. Due to the small size of typical ligands, relatively little free energy is available from ligand binding to overcome the often high energetic barrier of reshaping RNA structure. Instead, most riboswitches appear to take advantage of the directional and hierarchical folding of RNA by employing the ligand as a structural 'linchpin' to adjust the kinetic partitioning between alternate folds. In this model, even small, local structural and kinetic effects of ligand binding can cascade into global RNA conformational changes affecting gene expression. Single-molecule (SM) microscopy tools are uniquely suited to study such kinetically controlled RNA folding since they avoid the ensemble averaging of bulk techniques that loses sight of unsynchronized, transient, and/or multi-state kinetic behavior. This review summarizes how SM methods have begun to unravel riboswitch-mediated gene regulation.